ANALISIS TERHADAP KEBIJAKAN PEMERINTAH PROVINSI DKI JAKARTA TENTANG PENUTUPAN JALAN JATI BARU RAYA UNTUK PEDAGANG KAKI LIMA - Martin Hadinata; Tatang Ruchimat (Fakultas Hukum Universitas Tarumanagara, 2018)
Sidewalks are pedestrian paths that are generally parallel to the road and higher than the surface of the pavement to ensure the safety of the pedestrians concerned and Street Vendors (PKL) is a term to refer to the merchant invaders who carry out commercial activities over the area owned roads or sidewalks that should be intended for pedestrians. On December 22 Year 2017, the Provincial Government of DKI Jakarta imposed a new concept of structuring the Tanah Abang market area. Access to transportation until the placement of street vendors starts to be changed, there are some changes to the concept of Tanah Abang market area, the road along Tanah Abang station on Jati Baru Raya road will be closed, the second change of street vendors who usually sell in Tanah Abang market area will be moved to the front of the road in front of Tanah Abang station. Policies taken by the Provincial Government of DKI Jakarta proved to violate Article 12 of the Law of the Republic of Indonesia Number 38 Year 2004 concerning Roads, Article 128 Paragraph 3 of Law Number 22 Year 2009 concerning Road Traffic and Transportation. The DKI Jakarta Provincial Government in taking the decision to close Jalan Jati Baru Raya has no prior coordination with the Traffic Director of the Jakarta Metropolitan Police who is authorized about traffic in Jakarta.